Dynamic service provisioning mechanisms for next-generation optical internet - Yu, Xiaojun (2014)
Explosive Internet traffic growth over the past decades has enabled the rapid development and wide deployment of wavelength division multiplexing (WDM)-based networking technologies. At the same time, as IP/MPLS technology continues to gain popularity, it is widely believed that next-generation optical networks will adopt an IP/MPLS over WDM architecture with wavelength-routed WDM networks serving as the backbone. Since the capacity provided by a single wavelength channel in WDM networks is typically on the order of Gigabits per second (Gbps), while the bandwidth requirement of a request is typically much smaller than that, efficient schemes are desired to improve wavelength capacity utilization in WDM networks. This dissertation investigates several dynamic traffic provisioning problems with unicast and multicast traffic requests in the context of next-generation optical Internet. The main objective is to devise efficient mechanisms to optimize the overall network blocking performance. We first study the dynamic label switched path routing problem in an overlay IP/MPLS over WDM network. In such a network, the limited information exchanges between the two layers of the network, if not properly devised, will seriously degrade the network performance. We propose to learn from the historical data of lightpath setup costs maintained by the IP/MPLS layer integrated service provider (ISP) when making routing decisions. A novel historical data-learning scheme, called Existing Link First, is proposed. Simulation results demonstrate that the proposed method significantly improves the network performance. Next, we investigate the dynamic multicast traffic grooming problem in wavelength routed WDM networks. We conduct comprehensive comparisons between the performances of two classes of existing schemes, namely the lightpath-based methods and light-tree-based methods. Our comparison results show that the lightpath-based schemes typically achieve better blocking performances than the light-tree-based schemes. We study the results carefully and explain the underlying cause of our findings. Inspired by such observations, we then proceed to propose a new lightpath based algorithm called the lightpath fragmentation (LPF) method. Simulation results show that the LPF method consistently outperforms all existing methods under different traffic loads. By combining a data-learning scheme on the IP/MPLS layer to facilitate efficient routing and a lightpath fragmentation approach on the WDM layer to improve resource sharing, we propose in the third part of our work an overlay multicast provisioning (OMP) mechanism for dynamic multicast traffic grooming in overlay IP/MPLS over WDM networks. We show that OMP achieves much better blocking performances than all of the existing schemes. Further studies are carried out to determine the contributions of the data-learning scheme and lightpath fragmentation method, respectively, in various cases. Finally, we consider the problem of protecting subwavelength level multicast requests through dynamic traffic grooming in WDM networks. A new mechanism called lightpath fragmentation-based segment shared protection (LF-SSP) is proposed for protecting multicast requests at the connection level. By improving the efficiency of resource sharing in multicast traffic grooming and its corresponding protection process, LF-SSP manages to outperform all of the existing methods by achieving better blocking performance when supporting both sub-wavelength- and wavelength-level dynamic multicast requests with shared protection.